Deadly Retropharyngeal Abscess With Concurrent COVID-19 Infection: A Case Report - Nor Azirah Salahuddin; Muhammad Irsyad Mohamed Noor; Azreen Zaira Abu Bakar; Ahmad Anwaar Muhammad Saifullah; Nour Hanan Daniah Mohd Bakhit; Siti Asmat Md Arepen; Nor Eyzawiah Hassan (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2024)
Indexed by Scopus/ERA